2019
DOI: 10.3390/children6030046
|View full text |Cite
|
Sign up to set email alerts
|

Child Morbidity and Disease Burden in Refugee Camps in Mainland Greece

Abstract: The crisis conflicts in Syria have forced a lot of people to relocate and live in mainland Greece, where they are hosted in refugee camps. In the present study, our aim was to assess child morbidity and overall disease burden in two camps in northern Greece during a six-month winter period. A primary health care office was founded in each camp. Refugees of all ages with health problems were examined daily by specialty doctors. Cases were classified into two categories: Infectious or non-infectious. In total, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…A plethora of further analyses showed that refugee children are at particular risk for diseases such as depression, infections, or poorly managed chronic diseases [4,5,6,7]. We and others previously identified children arriving in Europe during the current crisis to be particularly vulnerable to physical trauma and infectious diseases during their flight [8,9,10,11,12,13]. Besides psychological and physical trauma during displacement, malnutrition, poor hygiene, and overcrowded living conditions further add to the particular risk of refugee children for increased morbidity [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of further analyses showed that refugee children are at particular risk for diseases such as depression, infections, or poorly managed chronic diseases [4,5,6,7]. We and others previously identified children arriving in Europe during the current crisis to be particularly vulnerable to physical trauma and infectious diseases during their flight [8,9,10,11,12,13]. Besides psychological and physical trauma during displacement, malnutrition, poor hygiene, and overcrowded living conditions further add to the particular risk of refugee children for increased morbidity [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Infants had better health than children or toddlers. There was no association between illness and gender [15].…”
Section: Child Healthmentioning
confidence: 71%
“…The international public health community is concerned about childhood morbidity in the refugee camps of Greece. Kampouras et al was one of the first groups to investigate and report on the disease burden of camps among children [15]. They divided the illnesses that occurred over the winter of 2016-2017 into infectious and non-infectious categories.…”
Section: Child Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Priority infectious diseases affecting refugees and other newly arriving migrants to high-income countries include tuberculosis (TB) (active and latent), HIV, hepatitis B, hepatitis C, vaccine-preventable diseases (such as measles, mumps, rubella, diphtheria, tetanus, pertussis, and Haemophilus influenzae type b), and parasitic infections (such as strongyloidiasis and schistosomiasis) [4,[22][23][24]. In the EU and EEA, infectious diseases are the most common cause of illness in migrant children living in refugee camps and other reception areas, including acute respiratory tract infections, outbreaks of vaccine-preventable diseases, such as measles, and skin infection (e.g., scabies, pediculosis); gastrointestinal infection (e.g., shigellosis); typhoid fever; hepatitis A; tuberculosis; and malaria [25,26]. In this article, we discuss the priority infectious disease affecting refugee children, review guidelines for evaluation and screening tests, and address preventative measures through immunizations.…”
Section: Introductionmentioning
confidence: 99%